2020
DOI: 10.1177/1363461520906028
|View full text |Cite
|
Sign up to set email alerts
|

Substance use, affective symptoms, and suicidal ideation among Russian, Somali, and Kurdish migrants in Finland

Abstract: Comorbidity of substance use with affective symptoms and suicidality has been well documented in the general population. However, population-based migrant studies about this association are scarce. We examined the association of affective symptoms and suicidal ideation with binge drinking, daily smoking, and lifetime cannabis use among Russian, Somali, and Kurdish migrants in comparison with the Finnish general population. Cross-sectional data from the Finnish Migrant Health and Wellbeing Study (Maamu, n = 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 94 publications
0
14
0
1
Order By: Relevance
“…SI can be influenced by multiple indicators among adolescents, like age, gender, mental disorders, educational levels, social support, interpersonal difficulties, and family conflict (Ahorsu et al, 2020;Salama et al, 2020;Xiao et al, 2019). In addition, a large body of studies suggested that childhood maltreatment is a salient risk factor for SI (Falgares et al, 2018;Stickley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…SI can be influenced by multiple indicators among adolescents, like age, gender, mental disorders, educational levels, social support, interpersonal difficulties, and family conflict (Ahorsu et al, 2020;Salama et al, 2020;Xiao et al, 2019). In addition, a large body of studies suggested that childhood maltreatment is a salient risk factor for SI (Falgares et al, 2018;Stickley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in our previous study 11% of Russian men and 51% of Kurdish men reported abstaining from alcohol use . Furthermore, we have indicated that comorbid affective symptoms are more common among substance using Kurds in particular . This study will expand previous knowledge on pre‐migration traumatic experiences, post‐migration perceived discrimination and substance use .…”
Section: Introductionmentioning
confidence: 54%
“…It includes 25 items on depressive and anxiety symptoms during the preceding week, rated on a scale from 1, ‘not at all bothered’ to 4, ‘extremely bothered’. Mean scores for the HSCL‐25 were calculated, and a cut‐off point of 1.75 was applied to create a dichotomized variable for clinically significant symptoms (no/yes), as previously used .…”
Section: Methodsmentioning
confidence: 99%
“…Among the studies with general samples, 37 [ 16 18 , 21 , 25 , 30 , 32 , 35 , 44 , 45 , 47 49 , 52 , 54 , 55 , 60 , 61 , 64 , 66 , 70 , 71 , 75 , 77 80 , 82 84 , 86 , 88 , 90 ] reported on the prevalence of suicidal ideation ( Table 4 ). The findings were ordered by prevalence timeframe and sub-grouped by population type.…”
Section: Resultsmentioning
confidence: 99%